Performance and meat quality attributes of broiler chickens fed onion skin extract and onion skin meal supplemented diets at the finisher stage (2018)
Aims: This study was carried out to investigate the meat quality attributes of broiler chickens fed onion skin extract and onion skin meal supplemented diets at the finisher stage. Study Design: The experiment employed a complete randomized design; all data generated were subjected to analysis of variance, P=0.05. Place and Duration of Study: The study was carried out at the Teaching and Research Farm of the University of Ibadan, Ibadan, Nigeria, between October and December, 2016 Methodology: Four experimental diets were formulated such that treatment 1 contained the basal diet with synthetic antioxidant, treatment 2 was a basal diet without any antioxidant, and treatment 3 was basal diet supplemented with 30g/kg of onion skin extract while treatment 4 contained basal diet supplemented with 100 g/kg of onion skin meal. One hundred and sixty eight broiler birds were randomly assigned to four treatments of six replicates each at seven birds per replicate. They were raised for 8 weeks. At the expiration of the experiment, three birds from each replicate were randomly selected, tagged, fasted, weighed and slaughtered. Carcass and organs were obtained and weighed. Samples for cooking loss, pH and cooking yield were taken. Thiobarbituric Acid Reactive Substances (TBARS) was employed to assess the shelf stability of the product. Aims: This study was carried out to investigate the meat quality attributes of broiler chickens fed onion skin extract and onion skin meal supplemented diets at the finisher stage. Study Design: The experiment employed a complete randomized design; all data generated were subjected to analysis of variance, P=0.05. Place and Duration of Study: The study was carried out at the Teaching and Research Farm of the University of Ibadan, Ibadan, Nigeria, between October and December, 2016 Methodology: Four experimental diets were formulated such that treatment 1 contained the basal diet with synthetic antioxidant, treatment 2 was a basal diet without any antioxidant, and treatment 3 was basal diet supplemented with 30g/kg of onion skin extract while treatment 4 contained basal diet supplemented with 100g/kg of onion skin meal. One hundred and sixty eight broiler birds were randomly assigned to four treatments of six replicates each at seven birds per replicate. They were raised for 8 weeks. At the expiration of the experiment, three birds from each replicate were randomly selected, tagged, fasted, weighed and slaughtered. Carcass and organs were obtained and weighed. Samples for cooking loss, pH and cooking yield were taken. Thiobarbituric Acid Reactive Substances (TBARS) was employed to assess the shelf stability of the product.